2007
DOI: 10.1016/j.pbb.2007.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil restores memory performance and neural activity impaired by sleep deprivation in mice

Abstract: Abstract:The original aims of our study have been to investigate in sleep-deprived mice, the effects of modafinil administration on spatial working memory, in parallel with the evaluation of neural activity level, as compared to non sleep-deprived animals. For this purpose, an original sleepdeprivation apparatus was developed and validated with continuous electroencephalography recording. Memory performance was evaluated using spontaneous alternation in a T-maze, whereas the neural activity level was estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 45 publications
3
46
0
Order By: Relevance
“…To the best of our knowledge, only our previous study has already shown that modafinil induced a retrograde memory-enhancing effect (Béracochéa et al 2003;Pierard et al 2007). More specifically, it was found that modafinil induced a faster emergence of a learning set rule, according to the amount of training (1 or 4 days) occurring before the injection.…”
Section: Behavioural Effects Of Modafinil In Rodents Tasksmentioning
confidence: 84%
See 1 more Smart Citation
“…To the best of our knowledge, only our previous study has already shown that modafinil induced a retrograde memory-enhancing effect (Béracochéa et al 2003;Pierard et al 2007). More specifically, it was found that modafinil induced a faster emergence of a learning set rule, according to the amount of training (1 or 4 days) occurring before the injection.…”
Section: Behavioural Effects Of Modafinil In Rodents Tasksmentioning
confidence: 84%
“…We recently showed that modafinil is able to restore neural activity and memory performance previously impaired by sleep deprivation in mice (Pierard et al 2007). Because modafinil was administered after sleep deprivation, this last result evidenced the retrograde effect of modafinil on memory retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, 6 h SD preceding acquisition of a water maze task impaired spatial memory in rats tested 24 h later, although it had not affected the learning curve during acquisition (Guan et al 2004), and a 10 h SD preceding a spontaneous alternation test impaired spatial working memory in mice (Pierard et al 2007). In human subjects a night of SD prior to learning, caused a deficit in the ability to encode new episodic memories, resulting in a worsening in retention (Yoo et al 2007).…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, recent research from rodent experiments has highlighted that sleep deprivation is associated with reduced neural activity within brain regions involved in memory (frontal cortex and hippocampus), emotion (amygdala), and regulation of the sleep-wake cycle (anterior hypothalamus and supraoptic nucleus) (Pierard et al 2007;Vecsey et al 2009;Hagwoud et al 2011). Disruption of any of these distinct facets of cognition by sleep deprivation may contribute to noteworthy errors in decision-making (reviewed by (Killgore 2010)).…”
Section: Sleep Deprivation Affects Higher-order Cognitive Processesmentioning
confidence: 99%